Improving resistance to lepidopteran pests and herbicide using Sanming dominant genic male sterile rice (Oryza sativa L.) - Li, Zhen; Liu, Xu; Zhang, Hua; Li, Pingbo; Yao, Fangyin (Frontiers in Plant Science, 2024)
In order to improve both resistance to lepidopteran pests and resistance to the herbicide imazethapyr in mainstay japonica varieties of the Huang-Huai rice region, Sanming dominant genic male sterile (S-DGMS) rice was used as a platform to facilitate the pyramiding of functional genes and the replacement of the genomic background. Twelve novel lines were developed, each carrying a crystal toxin gene conferring resistance to lepidopteran pests and the ALS627N allele conferring resistance to herbicide imazethapyr in the background of a mainstay japonica variety. The genomic background of the 12 novel lines was examined using 48 specified molecular markers, and each line carried less than two polymorphic markers relative to the corresponding mainstay variety. All 12 lines displayed high resistance to lepidopteran pests and the herbicide imazethapyr. The major agronomic traits of the 12 lines showed no difference relative to the responding mainstay variety when sprayed with pesticide. The popularization of the 12 japonica lines could reduce the use of pesticides and provide highly efficient control of weeds and weedy rice in the future, thus promoting the development of japonica rice production. Therefore, S-DGMS rice could be a powerful tool for the genetic improvement of target traits in rice.